PP.16.41: PHYSICAL ACTIVITY LEVEL AND AMBULATORY CONTROL OF HYPERTENSION. (June 2015) - Sosner, P.; Ott, J.; Steichen, O.; Bally, S.; Krummel, T.; Brucker, M.; Lequeux, B.; Dourmap-Collas, C.; Llaty, P.; Le Coz, S.; Baguet, S.; Miranne, A.; et al.
Abstract : Objective: Regular physical activity (PA) is a recommended component of treatment of hypertensive subjects, but its prescription is rare and most often insufficient. In addition, the PA level of hypertensive subjects remains unclear, even as methods of evaluation are growing up (subjective method using self-questionnaires or objective method using activity sensors). We aimed to assess the association between PA level and ambulatory control of high blood-pressure (BP) in 9 hypertension centres. Design and method: 85 hypertensive subjects were included (59 ± 14 years-old, 61% men, 12% smokers, 29% with diabetes, 58% with dyslipidaemia, 29% with a history of cardiovascular disease). Following their consultation, they were asked to realise home BP self-measurement (HBPM) during 7 days (2 in the morning + 2 evening) using a Microlife ® BP-A100-Plus device and a well-sized cuff. In addition, they wrote their daily activities on a dedicated form, in order to estimate the total calorie expenditure using Acti-MET strip (simplified tool extrapolated from the short version of the International Physical Activity Questionnaire, IPAQ). The subjects then completed a self-administered questionnaire called 'score of Dijon' with 30 points (distinguished active subjects with a score >20/30 from sedentary <10/30). Results: HBPM average was normal in 36 subjects (systolic/diastolic BP <135/85 mm Hg), 29% had white-coat effect, 3% masked hypertension. Compared to uncontrolled, subjects with normal HBPM were older and had a lower body mass index (Table 1). Also, they had a tendency (not significant) for a higher "score of Dijon". Thus, we noted a correlation between "score of Dijon" and the overall energy expenditure estimated with Acti-MET strip (Spearman's rho 0.340, p = 0.0021). Figure. No caption available. Conclusions: Our results demonstrate a 'tendency' for a higher level of declarative PA for subjects whose hypertension was controlled. This encourages us to continue with a study that would include more subjects, and which PA level would be assessed by wearing an objective method such as an accelerometer sensor device.